The Dynamics of Mass Media Resistance toward Google - Irwan Nugroho (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
The dominance of digital advertising by Google had an impact on decreasing mass media revenue. Meanwhile, Google was a search engine company on the internet that mostly relies on news content. During this decade, the mass media in America, The European Union, and Australia had demanded Google to pay for their content. The local authorities intend to create a balanced bargaining position among them. However, Google continued to refuse to pay on the grounds that it has brought heavy traffic to news publisher websites. In 2020, Google was finally willing to pay for news content by launching a News Showcase. This partnership was claimed to be profitable for publishers and readers. However, it had also been criticized because Google remained in charge of determining the terms and conditions. It also undermined The Copyright Act of European Union amendments designed to create fair negotiations between the mass media and Google.